1985
DOI: 10.1093/infdis/152.4.668
|View full text |Cite
|
Sign up to set email alerts
|

The Severe and Moderate Phenotypes of Heritable Mac-1, LFA-1 Deficiency: Their Quantitative Definition and Relation to Leukocyte Dysfunction and Clinical Features

Abstract: An inherited syndrome characterized by recurrent or progressive necrotic soft-tissue infections, diminished pus formation, impaired wound healing, granulocytosis, and/or delayed umbilical cord severance was recognized in four male and four female patients. As shown with subunit-specific monoclonal antibodies in immunofluorescence flow cytometry and 125I immunoprecipitation techniques, in addition to a NaB3H4-galactose oxidase labeling assay, granulocytes, monocytes, or lymphocytes from these individuals had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
264
0
3

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(276 citation statements)
references
References 0 publications
8
264
0
3
Order By: Relevance
“…5 Clinical severity is dependent on the CD18 expression levels with those patients having less than 1% of the normal CD18 levels being most affected, whereas patients with up to 10% of normal activity can make it to adulthood with medical care. 6 As LADaffected children often lack a suitable bone marrow donor 7 and the bone marrow transplant procedure has a significant treatment-related mortality, 8,9 gene therapy approaches for such patients are fully justified.…”
Section: The Diseasementioning
confidence: 99%
“…5 Clinical severity is dependent on the CD18 expression levels with those patients having less than 1% of the normal CD18 levels being most affected, whereas patients with up to 10% of normal activity can make it to adulthood with medical care. 6 As LADaffected children often lack a suitable bone marrow donor 7 and the bone marrow transplant procedure has a significant treatment-related mortality, 8,9 gene therapy approaches for such patients are fully justified.…”
Section: The Diseasementioning
confidence: 99%
“…Although these patients had a persistent leukocytosis, very few leukocytes accumulated at infected, necrotic lesions. In 1984 several groups demonstrated that these patients' leukocytes were missing CDt la,b,c/CD18 and subsequent work has demonstrated that the primary genetic defects are in CD18, the shared subunit (2)(3)(4)(5)23,24). Thus, the inability of leukocytes to adhere to endothelium or other particles because of an inherited defect in adhesive molecules prevents accumulation of leukocytes at sites of microbial invasion and results in severe, recurrent infections.…”
Section: Integrinsmentioning
confidence: 99%
“…Considering the protective function of immune response, to determine which immune cell(s) or factor(s) are involved in the destruction of periodontium rather than protection is important to predict disease course and plan treatment. People with defects in neutrophil function demonstrated that neutrophil has a pivotal role in the protection from periodontitis (Cianciola et al, 1977;Clark et al, 1977;Anderson et al, 1985). Chronically inflamed periodontal tissues are infiltrated densely with lymphocytes as well as phagocytic leukocytes.…”
Section: Introductionmentioning
confidence: 99%